Advances in taxation. Vol. 18 - Luttman, Suzanne (Emerald, 2008)
This title addresses various aspects of taxation, including tax policy issues at the federal, state, local, and international levels. This series covers topics of compliance, computer usage, education, legal, and planning, or policy issues.
Addresses various aspects of taxation, including tax policy issues at the federal, state, local, and international levels.
Keywords: Taxation -- United States.; elektronické knihy; electronic books